Inclusive and Empowering Discourse in an Early Childhood Literacy Classroom with Indigenous Students - Thwaite, Anne (The Australian Journal of Indigenous Education, 2007)
Abstract This paper presents an analysis of the classroom discourse and strategies of Marcia, an early childhood teacher of a class with a high percentage of Indigenous Australian students. These students have been demonstrably successful on standardised literacy tests, which is not the case for Indigenous students in general in Australia (e.g., MCEETYA, 200). It will be suggested here that Marcia’s approach and relationships with the students, as constructed in her discourse, have been a large contributing factor in this success. Marcia’s discourse can be described as both inclusive and empowering and, as such, it will be proposed that awareness of her techniques may be of benefit to teachers who are working with groups whom education systems tend to marginalise and disempower. Marcia’s lessons were observed as part of the project, “Teaching Indigenous Students with Conductive Hearing Loss in Remote and Urban Schools of Western Australia”. This project was based in Kurongkurl Katitjin, School of Indigenous Studies, at Edith Cowan University, Perth, Western Australia, and was funded by an Australian Research Council Strategic Partnerships with Industry [SPIRT] Grant and the industry partners: Department of Education of Western Australia, Catholic Education Commission of Western Australia and Aboriginal Independent Community Schools, Western Australia.